Juventude e projeto de vida: Novas perspectivas em orientação profissional - Mandelli, Maria Teresa; Soares, Dulce Helena Penna; Lisboa, Marilu Diez [UNESP] (My University, 2011)
The article discusses youth and life project topics, linking them to the concepts of socio-historical psychology and sociology of youth, when it comes to understanding how subjectivity is constituted. It is a theoretical reflection on life project category applied to career counseling of young people from economic disadvantaged class. This category ponders the dynamics of the constitution of identities and can be applied in career counseling with youth inclusion programs in the world of work. The professional counselor, assisting young people in their insertion in the world market and in building their careers, participates in building their life projects. Therefore, according to the theories that support this article, young people, having greater autonomy, will be the leading figures of their integration process to build their future.
Youth and life project: New perspectives in career counseling
Keywords: Career counseling; Identity; Life project; Youth